Testing the Minimum System Entropy and the Quantum of Entropy - Uwe Hohm; Christoph Schiller (Entropy, 2023)
Experimental and theoretical results about entropy limits for macroscopic and single-particle systems are reviewed. All experiments confirm the minimum system entropy <semantics>S⩾kln2</semantics>. We clarify in which cases it is possible to speak about a minimum system entropy<semantics>kln2</semantics> and in which cases about a quantum of entropy. Conceptual tensions with the third law of thermodynamics, with the additivity of entropy, with statistical calculations, and with entropy production are resolved. Black hole entropy is surveyed. Claims for smaller system entropy values are shown to contradict the requirement of observability, which, as possibly argued for the first time here, also implies the minimum system entropy <semantics>kln2</semantics>. The uncertainty relations involving the Boltzmann constant and the possibility of deriving thermodynamics from the existence of minimum system entropy enable one to speak about a general principle that is valid across nature.